The Different Length in Releasing Umbilical Cord between the Treatment with Breast Milk Topical Method and Dry Gauze Method for Newborns Baby - Dwi Ediningtyas; Sri Widatiningsih; Siti Chunaeni (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
This study is to evaluate the efectivity breast milk topical method and dry gauze method towards the length of period of the umbilical release for newborn babies. The design of this research was postest two group experimental design. The subjects were 20 newborns used topical breast milk method umbilical cord treatment and 20 newborns used dry gauze method. The length of release were counted in hours started from the birth of the babies. The result is, there is a significant difference in length in releasing umbilical cord between the treatment with breast milk topical method and dry gauze method for newborn babies (p=0.007). In fact, the breast milk topical method is 80,50 hours more effective than dry gauze method.